1997
DOI: 10.1046/j.1537-2995.1997.37597293882.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mobilization of CD34+ cells in normal donors treated with filgrastim

Abstract: Donor variables correlated with CD34+ cell yield only weakly, so no particular clinical characteristic can be used to exclude an individual as a PBPC donor if he or she is otherwise suitable for the apheresis procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
87
4
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 24 publications
10
87
4
1
Order By: Relevance
“…In spite of that fact, fewer mononuclear cells were mobilized during the second rhG-CSF course, resulting in a poor CD34 ϩ yield. Thus, contrary to previous data indicating a correlation between pre-apheresis leukocyte count and CD34 ϩ yields in single mobilization, 5 in short-term second mobilizations this parameter might not have such a good predictive value. Together, these data suggest that an 8-day interval between commencement of rhG-CSF mobilizations, permits the release of mature cells to the blood stream, but is not sufficient for reconstitution of the stem cell compartment to allow harvesting of sufficient cells to ensure hematopoietic engraftment after transplantation.…”
Section: Discussioncontrasting
confidence: 96%
“…In spite of that fact, fewer mononuclear cells were mobilized during the second rhG-CSF course, resulting in a poor CD34 ϩ yield. Thus, contrary to previous data indicating a correlation between pre-apheresis leukocyte count and CD34 ϩ yields in single mobilization, 5 in short-term second mobilizations this parameter might not have such a good predictive value. Together, these data suggest that an 8-day interval between commencement of rhG-CSF mobilizations, permits the release of mature cells to the blood stream, but is not sufficient for reconstitution of the stem cell compartment to allow harvesting of sufficient cells to ensure hematopoietic engraftment after transplantation.…”
Section: Discussioncontrasting
confidence: 96%
“…Our data, as well as that reported by others, 15,34,35 clearly indicate that some volunteers are intrinsically poor responders to rhG-CSF, although due to low numbers, no specific characteristics could be identified as a predictive factor for response to rhG-CSF administration in these 'poor' mobilizers. In these cases, alternative approaches to PBPC mobilization need to be investigated.…”
Section: Discussionsupporting
confidence: 82%
“…11 It has been demonstrated that, at least for rhG-CSF at doses between 5 and 10 g/kg/day, a dose-response relationship does exist with regard to the yield of CD34 ϩ cells. 12 Although rhG-CSF doses up to 24 g/kg/day have been reported, 13 experience with such high amounts remains limited. The purpose of this dose escalating study was to determine whether escalating split doses of lenograstim ranging from 8 to 15 g/kg do result in an increase in the number of CD34 ϩ cells harvested and whether higher doses of G-CSF might allow collection earlier.…”
mentioning
confidence: 99%